ENGINE PERFORMANCE USING GASOLINE ETHANOL MIXTURE TOWARD OPTIMUM HYBRIDNESS ON HYBRID POWER SYSTEM 2.8 HP - Mahendra, Sena (PAWIYATAN, 2013)
The research was conducted to determine the changeover optimum hybridity level on hybrid power system. The writer used two kinds of fuel as the comparison against premium. Fuel number one is the mixture gasoline and ethanol (gasohol) 5% (E-5) and the second fuel is the mixture gasoline and ethanol (gasohol) 10% (E-10). Both are at various levels of torque. The results show that the mixture 10% gasohol (E-10) increase the hybridity level. The optimum hybridity level at 3.5 Nm of torque shows an increase of 42%. The same torque decrease power consumption only 10.2% and it showed the increased of fuel consumption in 9%.ÃÂ Keywords : Hybrid, hybridness , fuel consumption, optimum, ethanol mixtureÃÂ